Form of Communication for Teaching Bajo Children The Local Values in Utilizing Natural Marine Resources - Jumaidin, La Ode; Irawati, Irawati; Udu, Sumiman; Hasddin, Hasddin; Husen, Osu Oheoputra (el Harakah: Jurnal Budaya Islam, 2024)
The issue behind the research on the Bajo tribe is the lack of understanding regarding the forms of communication used by the tribe to impart knowledge about local wisdom concerning the sustainable use of coastal and marine resources. Therefore, the aim of this research is to identify both the forms of local wisdom and the communication methods used to educate Bajo children about the sustainable use of coastal resources, ensuring the preservation of the Bajo tribe's cultural identity. The study was conducted among the Bajo tribe living along the coast of the Tiworo Strait in Muna Regency and West Muna Regency. The research informants consisted of 15 individuals, purposively selected, including elders and tribal leaders. The findings revealed that the local wisdom being passed down includes traditional management of coastal natural resources, such as: (a) the mammia kadialo tradition, involving fishing practices, which include palilibu, pongka, and sasakai; (b) traditional methods of fishing, including missi, ngarua, mana (archery using traditional tools), and nyuluh/balobe (also called ngobor); (c) the Pamali tradition, which involves specific taboos at certain times and places; and (d) the Maduai Pinah ritual, a form of worship for the "sea ruler" believed to protect and provide natural resources. Communication methods used to teach Bajo children about the utilization of natural resources include intrapersonal communication, interpersonal communication, and group communication. Permasalahan yang mendasari penelitian tentang suku Bajo adalah kurangnya pemahaman mengenai bentuk-bentuk komunikasi yang digunakan oleh suku tersebut dalam menyampaikan pengetahuan tentang kearifan lokal terkait pemanfaatan sumber daya pesisir dan laut secara berkelanjutan. Oleh karena itu, tujuan penelitian ini adalah untuk mengidentifikasi bentuk kearifan lokal dan metode komunikasi yang digunakan dalam mendidik anak-anak suku Bajo tentang pemanfaatan sumber daya pesisir yang berkelanjutan, sehingga dapat menjaga kelestarian identitas budaya suku Bajo. Penelitian ini dilakukan pada suku Bajo yang tinggal di sepanjang pesisir Selat Tiworo di Kabupaten Muna dan Kabupaten Muna Barat. Informan penelitian terdiri dari 15 orang yang dipilih secara purposive, termasuk para tetua dan kepala suku. Hasil penelitian mengungkapkan bahwa kearifan lokal yang diwariskan meliputi pengelolaan tradisional sumber daya alam pesisir, antara lain: (a) tradisi mammia kadialo, yang melibatkan praktik penangkapan ikan, termasuk palilibu, pongka, dan sasakai; (b) cara tradisional menangkap ikan, seperti missi, ngarua, mana (memanah dengan alat tradisional), serta nyuluh/balobe (juga disebut ngobor); (c) tradisi Pamali, yaitu larangan pada waktu dan tempat tertentu; dan (d) ritual Maduai Pinah, yaitu penyembahan kepada "penguasa laut" yang diyakini melindungi dan menyediakan sumber daya alam bagi mereka. Metode komunikasi yang digunakan untuk mengajarkan anak-anak suku Bajo tentang pemanfaatan sumber daya alam meliputi komunikasi intrapersonal, komunikasi interpersonal, dan komunikasi kelompok.